The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
17th AIAA International Space Planes and Hypersonic Systems and Technologies Conference 2011
DOI: 10.2514/6.2011-2393
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Uncertainty Quantification in Multidisciplinary Analysis of a Reusable Launch Vehicle

Abstract: The objective of this study was to apply a recently developed uncertainty quantification framework to the multidisciplinary analysis of a reusable launch vehicle (RLV). This particular framework is capable of efficiently propagating mixed (inherent and epistemic) uncertainties through complex simulation codes. The goal of the analysis was to quantify uncertainty in various output parameters obtained from the RLV analysis, including the maximum dynamic pressure, cross-range, range, and vehicle takeoff gross wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…In recent studies [11,12,14,16,17], the polynomial chaos method has been used as a means of UQ over traditional methods, such as Monte Carlo, for its computational efficiency. Polynomial chaos is a surrogate modeling technique based on the spectral representation of the uncertainty.…”
Section: Uncertainty Quantification Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies [11,12,14,16,17], the polynomial chaos method has been used as a means of UQ over traditional methods, such as Monte Carlo, for its computational efficiency. Polynomial chaos is a surrogate modeling technique based on the spectral representation of the uncertainty.…”
Section: Uncertainty Quantification Methodologymentioning
confidence: 99%
“…The first objective is to demonstrate the use of stochastic response surfaces based on nonintrusive polynomial chaos (NIPC) for efficient quantification of uncertainty in system performance metrics, as well as performance boundaries. Previous work by Hosder and Bettis [11] and Bettis et al [12], as well as Hosder et al [13,14], in the area of using stochastic expansions based on NIPC as a means of efficient uncertainty quantification (UQ) has been extensively investigated. These works included studies involving the propagation of both aleatory (inherent) and epistemic uncertainties through a variety of stochastic model problems.…”
mentioning
confidence: 99%
“…Recently, Eldred et al [31] have demonstrated mixed UQ using different methods like interval optimization, second-order probability [19,28,30,32] and DSTE. They investigated the use of nested sampling for mixed UQ, where each sample taken from the epistemic distributions at the outer loop results in an inner loop sampling over the aleatory probability distributions.…”
Section: Dste For Epistemic and Mixed Uncertainty Representationmentioning
confidence: 99%
“…In this work, we focus on generalized polynomial chaos using the Wiener-Askey scheme, which is explained in detail by Xiu and Karniadakis [44]. In previous years, many researchers have utilized polynomial chaos theory in stochastic computations [26][27][28]35,45,46]. In non-intrusive polynomial chaos expansion (PCE), simulations are used as black boxes and the calculation of chaos expansion coefficients is based on a set of simulation response evaluations.…”
Section: Point-collocation Non-intrusive Polynomial Chaosmentioning
confidence: 99%
See 1 more Smart Citation